2008
DOI: 10.3382/ps.2008-00105
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Knowledge and Risk Perceptions of Avian Influenza

Abstract: This study examined consumer risk perceptions and knowledge of avian influenza and its linkage to behavioral changes in chicken consumption. A consumer survey was administered in 3 metropolitan areas in Taiwan in 2007. Multivariate analyses were utilized in this study to analyze data. Findings in this study indicated that respondents who were more knowledgeable of avian influenza with relatively high levels of risk perceptions would be likely to stay away from birds and the crowd. Respondents with relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…A series of food scares, such as avian influenza, chicken meat contaminated with Salmonella, Campylobacter, and overuse of antibiotics in chicken has increased consumer concerns about the consumption of chicken. Amongst these food risks in chicken meat, microbiological risk causes consumers most concern (Yeung and Morris, 2001;Yeung and Yee, 2002;Gstraunthaler and Day, 2008;Hsu et al, 2008;Leppin and Aro, 2009;Voeten et al, 2009).…”
Section: Consumer Perceptions Of Poultry Meatmentioning
confidence: 99%
“…A series of food scares, such as avian influenza, chicken meat contaminated with Salmonella, Campylobacter, and overuse of antibiotics in chicken has increased consumer concerns about the consumption of chicken. Amongst these food risks in chicken meat, microbiological risk causes consumers most concern (Yeung and Morris, 2001;Yeung and Yee, 2002;Gstraunthaler and Day, 2008;Hsu et al, 2008;Leppin and Aro, 2009;Voeten et al, 2009).…”
Section: Consumer Perceptions Of Poultry Meatmentioning
confidence: 99%
“…In Taiwan, people have the habit of shopping at traditional markets for live poultry [10], and such traditional markets with live chicken for sale provide a possible AI viral reservoir [11], thereby placing traditional market workers and shoppers at risk for contracting AI. Poultry are usually selected and purchased by shoppers while they are still alive and slaughtered on site as shoppers in Taiwan commonly believe that live poultry preserves the freshness [11]. During the purchasing process, shoppers may come into contact with live poultry, thereby exposing shoppers to risk of contracting AI, and thus it is important that shoppers wash their hands after any contact with poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a telephone survey in the Hong Kong general population examined participants' AI risk perception in relation to their live chicken purchasing behavior [21]. Similarly, a study in Taiwan conducted by marketing and business management researchers assessed consumer knowledge and risk perceptions of AI in association with chicken consumption behavior, instead of AI preventive behavior under the threat of AI [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers who bought chicken at least once a month had a higher risk perception of AI than those who buy chicken at least once every week. Interestingly, a study in Taiwan found that consumers with relatively low levels of AI knowledge were likely to prefer not eating chicken at all under a possible threat of AI infection and those with low risk perception levels would be more likely to maintain usual chicken consumption than those with high risk perception levels if outbreaks of AI occurred [188]. This suggests that government administration and industry managers can design effective information communication for educational purposes to prevent a drop-in revenue due to the reduced demand and informing consumers about the safety of chicken products and proper cooking practices.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents with relatively low levels of AI knowledge were likely to prefer not eating chicken at all under a possible threat of AI outbreaks. Respondents with low risk perception levels would be more likely to maintain usual chicken consumption than those with high risk perception levels if outbreaks of AI occurred [188].…”
Section: Knowledge Attitudes and Practices (Kap) Of Poultry Workers mentioning
confidence: 99%